2007
DOI: 10.1534/genetics.107.073429
|View full text |Cite
|
Sign up to set email alerts
|

Using Reporter Gene Assays to IdentifycisRegulatory Differences Between Humans and Chimpanzees

Abstract: Most phenotypic differences between human and chimpanzee are likely to result from differences in gene regulation, rather than changes to protein-coding regions. To date, however, only a handful of human-chimpanzee nucleotide differences leading to changes in gene regulation have been identified. To hone in on differences in regulatory elements between human and chimpanzee, we focused on 10 genes that were previously found to be differentially expressed between the two species. We then designed reporter gene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
(68 reference statements)
1
11
0
Order By: Relevance
“…In a number of cases, these studies also pointed to possible connections between interspecies differences in gene regulation and differences in ultimate physiological or morphological phenotypes (Rockman et al 2005;Loisel et al 2006;Pollard et al 2006;Prabhakar et al 2008;Warner et al 2009;Babbitt et al 2010b). However, we still know little about the relative importance of different regulatory mechanisms to interspecies differences in gene expression levels (Chabot et al 2007;Blekhman et al 2009). In particular, little is known about the relative contribution of changes in epigenetic modifications to regulatory variation in primates.…”
Section: Omparative Studies Of Gene Expression Havementioning
confidence: 99%
“…In a number of cases, these studies also pointed to possible connections between interspecies differences in gene regulation and differences in ultimate physiological or morphological phenotypes (Rockman et al 2005;Loisel et al 2006;Pollard et al 2006;Prabhakar et al 2008;Warner et al 2009;Babbitt et al 2010b). However, we still know little about the relative importance of different regulatory mechanisms to interspecies differences in gene expression levels (Chabot et al 2007;Blekhman et al 2009). In particular, little is known about the relative contribution of changes in epigenetic modifications to regulatory variation in primates.…”
Section: Omparative Studies Of Gene Expression Havementioning
confidence: 99%
“…The two genes in this category with smallest P-values are MYOM1, a structural protein defining the M-Band of the sarcomere, and MYH1, which encodes a myosin heavy chain of skeletal muscle, and variants are associated with risk of colorectal cancer (Jenkins et al 2006). Two further musclerelated genes are among the 15 most extreme genes: MYBPHL, which contains functional promoter differences between humans and chimpanzees (Chabot et al 2007), and PAMR1 (also known as DKFZP586H2123), a regeneration associated muscle protease.…”
Section: Excess Of High Frequency-derived Alleles (Mwu-high)mentioning
confidence: 99%
“…Moreover, a number of studies have shown that evolutionary turnover of regulatory elements is a common feature of eukaryotic genomes with examples in yeast (Tanay et al 2005;Borneman et al 2007;Tuch et al 2008), Drosophila , zebrafish (McGaughey et al 2008), and mammals (Dermitzakis and Clark 2002;Birney et al 2007;Chabot et al 2007;Odom et al 2007;Jegga et al 2008).…”
mentioning
confidence: 99%